Internal Fixation of Osteochondritis Dissecans Lesions in the Patellofemoral Joint - Nuelle, Clayton W.; Farr, Jack (The Journal of Knee Surgery, 2018)
Osteochondritis dissecans (OCD) lesions of the patellofemoral joint can be difficult to identify and treat. Asymptomatic or stable lesions in skeletally immature patients may be treated nonoperatively, but symptomatic lesions often require surgical intervention. Evidence of instability should be carefully evaluated with preoperative magnetic resonance imaging or computed tomography arthrogram. Careful preoperative planning is necessary to ensure the appropriate surgical approach and implants are selected for surgical management. Multiple techniques have been described, but internal fixation of both “classic” and cartilage-only OCD lesions has been shown to have strong outcomes in managing these difficult cases.
Keywords: osteochondritis dissecans; internal fixation; patellofemoral